2022
DOI: 10.3390/buildings12081231
|View full text |Cite
|
Sign up to set email alerts
|

Shaking Table Test Research on the Influence of Center-Hung Scoreboard on Natural Vibration Characteristics and Seismic Response of Suspen-Dome Structures

Abstract: The center-hung scoreboard is a large electronic display device, that usually has a significant weight and is flexibly suspended from the roof of the gymnasium. The suspen-dome structure is one of the common roof structures of gymnasiums. In order to investigate the effect of the center-hung scoreboard on the natural vibration characteristics and seismic response, including acceleration, displacement, and strain, of the suspen-dome structure and considering that the dynamic behavior of the structure under seis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, this study only focuses on the suspend-dome structure, and the research on single-layer spherical reticulated shells has not been involved. [26,27].…”
Section: Seismic Response Analysis Methodsmentioning
confidence: 99%
“…However, this study only focuses on the suspend-dome structure, and the research on single-layer spherical reticulated shells has not been involved. [26,27].…”
Section: Seismic Response Analysis Methodsmentioning
confidence: 99%
“…In practice, a safety distance of about 1.0 m is reserved between the CHS and the support platform, and a sling length is selected every 0.5 m among 1.0 m and 9.0 m. Te length of the sling is taken as 0.0 m when the CHS is simplifed as fxed masses on the suspension nodes on the support platform. Since most of the CHSs used in recent years exceed 20 t and the heaviest ones have exceeded 55 t [23,24], the weight is selected every 5 t among 20 t and 60 t.…”
Section: Fe Modelsmentioning
confidence: 99%
“…In the past decade, with the development of professional sports events and other activities, the number of center-hung scoreboard (CHS) applications has increased signifcantly [23]. Te CHS is a large display device hanging in the center of the roof structure, and the heaviest CHS is about 55 t [24]. Xue et al conducted a shaking table test on a 94 m suspendome structure with a 30 t CHS and found that the CHS made a great increase on axial forces and node acceleration under seismic motions [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the modulus of elasticity of the spiral wire ropes is lower than that of structural steel, which increases their deformability [21,22]. It should be noted that the cylindrical surface of such suspension structures complicates their construction, operation, and maintenance, especially under wind loads [23][24][25]. Dynamic loads also have a great influence on the behaviour of suspended structures [26,27].…”
Section: Introductionmentioning
confidence: 99%